Effectiveness of Contralaterally Controlled Functional Electrical Stimulation versus Neuromuscular Electrical Stimulation on Upper Limb Motor Functional Recovery in Subacute Stroke Patients: A Randomized Controlled Trial - Songhua Huang; Peile Liu; Yinglun Chen; Beiyao Gao; Yingying Li; Chan Chen; Yulong Bai (Neural Plasticity)
Purpose. To compare the effectiveness of contralaterally controlled functional electrical stimulation (CCFES) versus neuromuscular electrical stimulation (NMES) on motor recovery of the upper limb in subacute stroke patients. Materials and Methods. Fifty patients within six months poststroke were randomly assigned to the CCFES group (n=25) and the NMES group (n=25). Both groups underwent routine rehabilitation plus 20-minute stimulation on wrist extensors per day, five days a week, for 3 weeks. Fugl-Meyer Assessment of upper extremity (FMA-UE), action research arm test (ARAT), Barthel Index (BI), and surface electromyography (sEMG) were assessed at baseline and end of intervention. Results. After a 3-week intervention, FMA-UE and BI increased in both groups (p<0.05). ARAT increased significantly only in the CCFES group (p<0.05). The changes of FMA-UE, ARAT, and BI in the CCFES group were not greater than those in the NMES group. The improvement in sEMG response of extensor carpi radialis by CCFES was greater than that by NMES (p=0.026). The cocontraction ratio (CCR) of flexor carpi radialis did not decrease in both groups. Conclusions. CCFES improved upper limb motor function, but did not show better treatment effect than NMES. CCFES significantly enhanced the sEMG response of paretic extensor carpi radialis compared with NMES, but did not decrease the cocontraction of antagonist.